Entwicklungstendenzen landwirtschaftlicher Familienbetriebe in Russland seit 1990; Development trends in family farming in Russia since 1990 - Katja Bruisch (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2007)
An die russische Agrarreform der 1990er Jahre knüpfte sich die Erwartung, dass entsprechend der Erfahrung in westlichen Staaten landwirtschaftliche Familienbetriebe (Fermer-Betriebe) an die Stelle der staatlichen Großbetriebe treten und einen Aufschwung in der russischen Landwirtschaft auslösen würden. Entgegen dieser Erwartungen ist der russische Fermer-Sektor bis heute verhältnismäßig schwach entwickelt, während die Landwirtschaft als eines der wichtigsten Problemfelder der russischen Innenpolitik gilt. Im vorliegenden Discussion Paper werden die für die Entstehung des Fermer-Sektors relevanten Aspekte der russischen Agrarreform nachvollzogen sowie auf der Grundlage russischer Statistiken die gegenwärtige Lage der russischen Landwirtschaft analysiert. Im Discussion Paper werden weiterhin die in der russischen Debatte angeführten Argumente für die Überlegenheit von Fermer-Betrieben und verschiedene Erklärungsansätze für die eher unbedeutende Rolle des russischen Fermer-Sektors vorgestellt. – – The reform of Russian agriculture at the beginning of the 1990s was accompanied by high expectations towards the rapid establishment of private family farms. These farms were assumed to replace inefficient state farms and enhance the competitiveness of Russian agriculture. Despite these expectations, family farming is still a small sector in Russia, while agriculture remains one of the most critical problems in Russian politics. This discussion paper provides an overview of the relevant stages of agricultural reform during the 1990s. Based on Russian statistics, it provides an insight into the current state of Russian agriculture, which is characterised by the coexistence of the former kolkhozes and small household farms pursuing subsistence farming. Because the discussions on the intended fermerization of Russian agriculture have highly been ideologized, the paper provides some of the key arguments for family farming, which have been stressed in Russian discussions. The article concludes with several explanations for the modest growth of Russian family farming, including some approaches from social sciences, which should complement purely economic approaches.
urn:nbn:de:gbv:3:2-3887
Keywords: P25; Q12; Q15; 330; Russia; transitional economies; agricultural reform; family farms; Russland; Transformation; Agrarreform; Familienbetriebe